Diclofenac Transdermal Patch: A Potential Ingress to Maxillofacial Surgery - Perepa, Anisha (J Maxillofac Oral Surg, 2016)
PURPOSE: To evaluate the analgesic efficacy of a diclofenac transdermal patch with diclofenac intra muscular injection in the immediate postoperative period in patients undergoing major oral surgical procedures. MATERIALS AND METHODS: Subjects who underwent bijaw surgeries for surgical correction of various dentofacial deformities were included. Sixty such patients who belonged to the above entity were randomly categorized into two groups from Jan 2012–Aug 2015. Group A (study group) received a single dose of 100 mg transdermal diclofenac patch, Group B (control group) received 75 mg intramuscular diclofenac and tramadol HCl 2 mg/kg body wt was used as rescue analgesic in the immediate post operative phase. The analgesic efficacy of the drugs are evaluated on periodic patient’s perception of pain in the immediate postoperative phase of 2nd, 6th, 12th, 24th and 48 hours. RESULTS: The mean VAS score in Group A was 2, mean duration of analgesia was 16 h 9 min, and in Group B the mean VAS score was 4, duration of analgesia was 8 h and 4 min. Tramadol HCl was given as rescue analgesia in 22 % (6) of patients belonging to Group A. None of the patients from both the groups reported local complications. CONCLUSION: A noninvasive application of a single dose of 100 mg transdermal diclofenac patch is more effective than intramuscular diclofenac (75 mg) in the immediate post operative phase, without any significant side-effects is a novel ingress into the field of oral and maxillofacial surgery for post operative pain management.